(untitled) (Journal of Asian Development Studies, 2025)
This study investigates the effect of technology-enhanced collaborative writing instruction on the motivation of Pakistani university students learning English as a second language (ESL). Adopting a quantitative quasi-experimental design, 50 participants were divided equally into an experimental group, which received instruction through digital collaborative platforms, and a control group, which was taught using conventional methods. The intervention spanned four weeks, during which pretest and post-test data were collected using the Second Language Writing Motivation Scale (Waller & Papi, 2017). Results from independent samples t-tests indicated a statistically significant increase in writing motivation among students exposed to technology mediated collaborative instruction compared to their counterparts. These findings highlight the motivational benefits of integrating technology in collaborative writing settings, suggesting that digital tools can play a crucial role in fostering student engagement and enthusiasm in ESL academic writing. Future research should investigate the longitudinal impacts and include diverse educational settings to enhance the generalizability of the results.